2012
DOI: 10.4161/cib.21304
|View full text |Cite
|
Sign up to set email alerts
|

Robots in the service of animal behavior

Abstract: As reading fiction can challenge us to better understand fact, using fake animals can sometimes serve as our best solution to understanding the behavior of real animals. The use of dummies, doppelgangers, fakes, and physical models have served to elicit behaviors in animal experiments since the early history of behavior studies, and, more recently, robotic animals have been employed by researchers to further coax behaviors from their study subjects. Here, we review the use of robots in the service of animal be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…As predicted, significant differences were obtained testing different combination of cues, highlighting the communication functions that visual cues, sent by the fish replica, and how much their changes/overlapping affect specific action patterns 35, 56, 60 . In agreement with other researches 61, 62 , our observations revealed that the B .…”
Section: Discussionsupporting
confidence: 63%
“…As predicted, significant differences were obtained testing different combination of cues, highlighting the communication functions that visual cues, sent by the fish replica, and how much their changes/overlapping affect specific action patterns 35, 56, 60 . In agreement with other researches 61, 62 , our observations revealed that the B .…”
Section: Discussionsupporting
confidence: 63%
“…Answers to questions so elaborately proposed by Wells (1977) in the light of vocal signalling activity during social behaviour and behavioural ecology have filled textbooks (Ryan 1985; Gerhardt and Huber 2002; Narins et al 2007) and further inspired groundbreaking research on acoustic communication systems (reviewed in Bee et al 2013) leading from the “matched filter hypothesis” (Capranica and Moffat 1983; Gerhardt and Schwarz 2001) to the use of robotic frogs to study signal function (e.g. Narins et al 2003; Klein et al 2012). Today’s biological research has started to look at the big picture and integrates several sensory modalities, communication behaviour, environmental influences, perceptual biases and mechanisms of the species under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The recent developments in free moving VR systems have opened doors for conducting new types of studies in collective behavior and social behavior, with developers of self-organizing robots already using the theories developed in collective behavior studies [78,85]. The robotics community is actively involved in development of new methods for studying behavior using interactive robots [45,47,50,84].…”
Section: Growing Support From Robotics and Computer Visionmentioning
confidence: 99%